Mad about the boy : the Noel Coward story [videorecording (DVD)] - Thompson, Barnaby; Coward, Noël, 1899-1973; Cumming, Alan, 1965-; Everett, Rupert; Olivier, Laurence, 1907-1989 (Kino Lorber, 2024)
The extraordinary life of playwright, singer, actor, composer, and director Noel Coward, who rose from poverty to stardom while keeping his sexuality a secret. Featuring Laurence Olivier, Maggie Smith, Frank Sinatra, Michael Caine and Lucille Ball. Narrated by Alan Cumming. With Rupert Everett as the voice of Noel Coward. Directed by Academy Awardʼ Nominee Barnaby Thompson.